2009
DOI: 10.1007/s00464-009-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of mental practice as a training strategy for laparoscopic surgery

Abstract: This is the first study to develop and validate MP as a novel training approach for laparoscopic surgery. Mental practice may be a time- and cost-effective strategy that improves surgeons' ability to visualize themselves performing a LC, increasing both their knowledge and confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 33 publications
1
100
1
5
Order By: Relevance
“…1 When applied to learning of a motor task, it activates synaptic connections in the motor frontal cortex that are normally activated by actual physical practice. 2 Neuroplasticity has been shown in other traditionally unimodal cortical areas such as the auditory and visual cortices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 When applied to learning of a motor task, it activates synaptic connections in the motor frontal cortex that are normally activated by actual physical practice. 2 Neuroplasticity has been shown in other traditionally unimodal cortical areas such as the auditory and visual cortices.…”
Section: Introductionmentioning
confidence: 99%
“…9 In surgery, MI as a technique of motor learning and practice has the theoretical advantages of being safe and inexpensive when compared with traditional learning in the operating theatre or in a simulation environment. 1 In addition, it has been shown to improve nontechnical aspects of surgical performance such as stress 10 and confidence. 1 Mental imagery is usually performed one on one with the learner and according to a script that contains visual, cognitive and kinaesthetic cues.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][15][16][17] The current evidence in surgical disciplines suggests that MP is a safe and cost-effective method for training novice surgeons in technical procedures. 8,16,17 A randomized controlled trial by Arora et al found MP to be beneficial for enhancing the imagery and performance of novice surgeons during a simulated laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…8,16,17 A randomized controlled trial by Arora et al found MP to be beneficial for enhancing the imagery and performance of novice surgeons during a simulated laparoscopic cholecystectomy. 5,8 Recently, Hayter et al found that warm-up using MP did not improve anesthesia CRM skills in novice anesthesia trainees during a simulated cardiac arrest. 11 This study found no significant difference in performance of CRM skills as assessed by the Ottawa GRS, or on the secondary outcomes of time to chest compressions, time to epinephrine administration, and time to blood administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation